Corporate Social Responsibility Performance and Stock Market Valuation in Indonesia - Soewignyo, Fanny (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
This study provides an analysis of the importance of corporate social responsibility performance towards the stock market valuation of companies listed on the Indonesia Stock Exchange. Indonesia is one of the destination countries for foreign investment; however, foreign investors are more interested in investing in socially responsible companies. Based on 237 observations from 2013 to 2018, the finding indicates a negative and significant effect of overall corporate social responsibility performance on stock market valuation measured by Tobin’s Q. This suggests that the stock market in Indonesia reacts negatively to high corporate social responsibility performance. The market considers corporate social responsibility as costly activities which can reduce company profit, thereby reducing shareholders’ wealth. Furthermore, considering the different categories of corporate social responsibility, the findings show a negative and significant effect of the community category on stock market valuation. This result indicates that the market is still not convinced that investing in the community can have a profitable impact. The effectiveness of community service activities is doubted by the market. Meanwhile, the three other categories, namely, employee, environment, and governance, do not have a significant effect on stock market valuation. This could be related to investors’ view that CSR activities are conducted just to comply with the requirement of law and regulations. It is not motivated by a sense of responsibility and ethical behavior. Thus, stock market valuation is unaffected by the rating, whether it is high or low. Therefore, public companies in Indonesia must be able to convince investors that the implementation of social responsibility is carried out in accordance with applicable laws and is effectively implemented. Keywords : Corporate social responsibility, stock market, performance, valuation, Indonesia